COVID-19 and female fertility: the flaws of Italian Law 40/2004 on assisted procreation in pandemic times - Marinelli, Susanna; Cucinella, Gaspare; Basile, Giuseppe (Acta Biomedica Atenei Parmensis, 2022)
Background and aim: SARS-CoV-2 has infected over 614 million people worldwide, killing more than 6.5 million. COVID-19 impact on fertility may have far-reaching ramifications, considering that only in Italy, over 20 million people have been infected, many more considering unconfirmed cases. Methods: The authors aimed to outline the repercussions of COVID-19 on female reproductive capabilities, through an analysis of underlying mechanisms and dynamics liable to cause long-term COVID-19 complications and sequelae, including direct virus-induced tissue damage. Results: The entry receptor for SARS-CoV-2, Angiotensin-converting enzyme 2 (ACE2) can be found in several tissues and organs within the human body, including ovaries, oocytes and placenta. In order to assess the fertility-damaging potential of the disease, it is necessary to clarify highly complex mechanisms such as the ovarian renin–angiotensin system (OVRAS) affecting ovarian physiology and dysfunction. COVID-19 and its potential to undermine the fertility prospects of millions cannot be underestimated. It is therefore essential for lawmakers to solve inconsistencies such as those in Italy’s Law 40/2004, which has been all but dismantled by Constitutional Court and European Court of Human Rights rulings, and cannot therefore offer a sufficient degree of certainty and reliability. Conclusions: When crafting novel, updated standards, norms and regulations to govern access to medically-assisted procreation, national leaders need to take into account the grave threat to fertility in a country such as Italy, which already has one of the world’s lowest birth rates, posed by COVID-19 in light of currently available research findings outlining its impact on reproductive capacity.